2020
DOI: 10.1016/j.cell.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoglobulin Superfamily Receptome Defines Cancer-Relevant Networks Associated with Clinical Outcome

Abstract: Highlights d The immunoglobulin superfamily (IgSF) interactome identifies over 500 receptor pairs d The IgSF interactome reveals receptor-ligand communities dysregulated in cancer d More than 60 receptor-ligand pairs confirmed using orthogonal methods d Interacting protein signatures are correlated with clinical outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 55 publications
(77 reference statements)
4
67
0
Order By: Relevance
“…However, using enzymatic readouts can add a high degree of signal amplification that allows for increased sensitivity. Therefore, the approach used to generate the largest ePPI networks to date uses pentamerization combined with an enzymatic β-lactamase colorimetric assay [37][38][39][40]. As for bead-based approaches, the specific readout can be magnetic, fluorescent or chemiluminescent depending on the specific screening method used [41,42].…”
Section: Target Presentation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, using enzymatic readouts can add a high degree of signal amplification that allows for increased sensitivity. Therefore, the approach used to generate the largest ePPI networks to date uses pentamerization combined with an enzymatic β-lactamase colorimetric assay [37][38][39][40]. As for bead-based approaches, the specific readout can be magnetic, fluorescent or chemiluminescent depending on the specific screening method used [41,42].…”
Section: Target Presentation Methodsmentioning
confidence: 99%
“…Using conditioned media involves direct capture of secreted protein or protein ectodomains in the absence of protein purification, thus minimizing potential inactivation of the proteins due to purification steps. The use of conditioned media can also save time and resources, helping to make the approaches more accessible to different laboratory and more amenable to scaling up [37][38][39][40].…”
Section: Target Presentation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, continuous update of current ligand-receptor libraries is necessary to cover more information of receptors, ligands and their interactions. Recently, receptor study of immunoglobulin superfamily (IGSFF) identified more than 60 new pairs of ligand -receptor [ 84 ]. The ligand-receptor pairs network is not completely understood and still needs futher exploration and improvement.…”
Section: Inadequacy Of Current Researchmentioning
confidence: 99%
“…A recent study undertook a large-scale ligand discovery campaign for Ig superfamily proteins and identified a new candidate binding partner for BTN2A1, FAM187B, plus eight new potential binding partners for BTN3A, so it will be very interesting to see if any of these molecules have a role in pAg or γδ T cell biology. 76 These are the next fundamental questions that must be answered in order to develop a better understanding of the pAg-sensing system, which is turning out to be highly distinct from all other characterized modes of Ag recognition.…”
Section: How Are Vγ 9vδ2 + γδ T Cell S S En S Ing Pag?mentioning
confidence: 99%